The macrophage-specific V-ATPase subunit ATP6V0D2 restricts inflammasome activation and bacterial infection by facilitating autophagosome-lysosome fusion. Issue 6 (3rd June 2019) - Xia, Yu; Liu, Na; Xie, Xiuxiu; Bi, Guoyu; Ba, Hongping; Li, Lin; Zhang, Jinxia; Deng, Xiaofei; Yao, Yao; Tang, Zhaohui; Yin, Binjiao; Wang, Jing; et al.
ABSTRACT: Macroautophagy/autophagy is a conserved ubiquitous pathway that performs diverse roles in health and disease. Although many key, widely expressed proteins that regulate autophagosome formation followed by lysosomal fusion have been identified, the possibilities of cell-specific elements that contribute to the autophagy fusion machinery have not been explored. Here we show that a macrophage-specific isoform of the vacuolar ATPase protein ATP6V0D2/subunit d2 is dispensable for lysosome acidification, but promotes the completion of autophagy via promotion of autophagosome-lysosome fusion through its interaction with STX17 and VAMP8. Atp6v0d2 -deficient macrophages have augmented mitochondrial damage, enhanced inflammasome activation and reduced clearance of Salmonella typhimurium . The susceptibility of atp6v0d2 knockout mice to DSS-induced colitis and Salmonella typhimurium -induced death, highlights the in vivo significance of ATP6V0D2-mediated autophagosome-lysosome fusion. Together, our data identify ATP6V0D2 as a key component of macrophage-specific autophagosome-lysosome fusion machinery maintaining macrophage organelle homeostasis and, in turn, limiting both inflammation and bacterial infection. Abbreviations : ACTB/β-actin: actin, beta; ATG14: autophagy related 14; ATG16L1: autophagy related 16-like 1 (S. cerevisiae); ATP6V0D1/2: ATPase, H+ transporting, lysosomal V0 subunit D1/2; AIM2: absent in melanoma 2; BMDM: bone marrow-derived macrophage; CASP1: caspase 1; CGD: chronic granulomatous disease; CSF1/M-CSF: colony stimulating factor 1 (macrophage); CTSB: cathepsin B; DSS: dextran sodium sulfate; IL1B: interleukin 1 beta; IL6: interleukin 6; IRGM: immunity-related GTPase family M member; KO: knockout; LAMP1: lysosomal-associated membrane protein 1; LC3: microtubule-associated protein 1 light chain 3; LPS: lipo-polysaccaride; NLRP3: NLR family, pyrin domain containing 3; PYCARD/ASC: PYD and CARD domain containing; SNARE: soluble N-ethylmaleimide-sensitive factor attachment protein receptor; SNAP29: synaptosomal-associated protein 29; SQSTM1/p62: sequestosome 1; STX17: syntaxin 17; TLR: toll-like receptor; TNF: tumor necrosis factor ; TOMM20: translocase of outer mitochondrial membrane 20; ULK1: unc-51 like kinase 1; VAMP8: vesicle-associated membrane protein 8; WT: wild type; 3-MA: 3-methyladenine